(untitled) (Journal of the College of Basic Education, 2022)
In this paper the differential transform method (DTM) is used to solve linear and nonlinear system of fuzzy differential equations. The approximate solution of the system is calculated in the form of a rapid convergent series using descriptions and properties of fuzzy set theory, this method captures the exact solution so to illustrate the ability and subtleties of this process, some systems of fuzzy differential equations are solved as numerical examples. A comparison of evaluated numerical results with the exact solutions for each fuzzy level set is displayed in the form of tables.